Peran Guru dalam Pendidikan Karakter Selama Pandemi Covid-19 di SMP Negeri 1 Sumbang - Ari Wijayanti; Sriyanto (Proceedings Series on Social Sciences & Humanities, 2021)
A teacher carries out a very noble task in addition to educating and providing transparency for students, namely making his students have good morals and noble character. Thus, a teacher must be able to make his students into noble human beings. Teachers play an important role even very important in terms of educating and providing transparency for their students. During the pandemic as it is today it is a challenge for teachers in Indonesia to instill character education. Character education is an effort to realize a generation of intelligent and good national (smart and good citizenship) or have a noble and Indonesian personality. The success of character education hints at learning not necessarily seen from the perspective of the cognitive realm alone but rather how the balance of the cognitive, affective, and psychomotor realms that estuary is to realize the whole human being. The condition of the Covid-19 pandemic is currently a challenge for the world of education, especially formal education in the efforts to education the character of the nation. Dominant learning is not done face-to-face, so it becomes a teacher's challenge in the process of character education. On the other hand, it will provide opportunities as learners in actualizing the values of character in the community in an effort to participate in the prevention and prevention of Covid-19. This research is descriptive qualitative with literature studies that seek to provide solutions to how character education is conducted while learning is still taking place by online methods in junior high school.